Arthroscopic-assisted reduction for Developmental Hip Dysplasia (DDH) through the sub-adductor and anterolateral portals; A 24-month follow-up prospective descriptive study - Amr Samir Rashwan; Mahmoud El-Desouky; Hassan Elbarbary; Mahmoud Abd Elhamid Madbouly; Ahmed Khedr (BMC Musculoskeletal Disorders, 2025)
Abstract Background Developmental dysplasia of the hip (DDH) encompasses a spectrum of pathological conditions, including dislocation, subluxation, and deformities of the femoral head and acetabulum. The optimal surgical approach for DDH remains a subject of debate. Successful treatment aims to achieve a stable concentric reduction and prevent future subluxation or dislocation. This study aims to assess the clinical and radiographic outcomes of arthroscopic-assisted surgical reduction of DDH in children aged from 6 months to 5 years old. Methods This prospective study included 57 patients with DDH (68 involved hips) between January 2019 and May 2021. They were treated with arthroscopic-assisted surgical reduction. Dega osteotomy was needed in 22 cases, femoral osteotomy and or shortening was necessary in 11 cases, and combined pelvic and femoral osteotomies were required in nine cases. We evaluated and followed all the patients clinically and radiologically, using Severin, modified Severin scores, Shenton line, and acetabular index measurement up to 24 months postoperatively. Results The mean age of the included patients was 26.9 months. The mean operative time was 54.7 (36–90) minutes. Clinical assessment using the modified Severin classification revealed that 53 hips (77.9%) were grade I and 11 hips (16.2%) were grade II at the end of the follow-up. Radiological evaluation using Severin classification revealed that 55 hips (80.9%) were in grade I, and 10 hips (14.7%) were in grade II. There was a statistically significant correlation between clinical and radiological grading (p < 0.001). Hip re-dislocation and avascular necrosis (AVN) were experienced in one and two cases, respectively. Conclusion These findings suggest that arthroscopic-assisted reduction for DDH, with or without osteotomies, is a promising technique with satisfactory clinical and radiographic outcomes and a low complication rate. However, given the single-center nature of this study and its relatively small sample size, these results should be interpreted with caution. Clinical Trial Registration (Retrospectively registered) Registration number: NCT06520436. 25-7-2024.